Adenovirus type 5 and 7 capsid chimera: fiber replacement alters receptor tropism without affecting primary immune neutralization epitopes. - Gall, J (1996)
The efficient uptake of adenovirus into a target cell is a function of adenovirus capsid proteins and their interaction with the host cell. The capsid protein fiber mediates high-affinity attachment of adenovirus to the target cell. Although the cellular receptor(s) for adenovirus is unknown, evidence indicates that a single receptor does not function as the attachment site for each of the 49 different serotypes of adenovirus. Sequence variation of the fiber ligand, particularly in the C- terminal knob domain, is associated with serotype-specific binding specificity. Additionally, this domain of fiber functions as a major serotype determinant. Fiber involvement in cell targeting and its function as a target of the host immune response make the fiber gene an attractive target for manipulation, both from the perspective of adenovirus biology and from the perspective of using adenovirus vectors for gene transfer experiments. We have constructed a defective chimeric adenovirus type 5 (Ad5) reporter virus by replacing the Ad5 fiber gene with the fiber gene from Ad7A. Using the chloramphenicol acetyltransferase reporter gene, we have characterized this virus with respect to infectivity both in vitro and in vivo. We have also characterized the role of antifiber antibody in the host neutralizing immune response to adenovirus infection. Our studies demonstrate that exchange of fiber is a strategy that will be useful in characterizing receptor tropism for different serotypes of adenovirus. Additionally, the neutralizing immune response to Ad5 and Ad7 does not differentiate between two viruses that differ only in their fiber proteins. Therefore, following a primary adenovirus inoculation, antibodies generated against fiber do not constitute a significant fraction of the neutralizing antibody population.